A controllable preparation method of cross-shrinkage COF nanocapsules and its application in selective separation of gold

The cross-crunched COF nanocapsule adsorbent is prepared through crystallization and recrystallization technology, which solves the problems of low adsorption capacity and slow adsorption rate of existing gold adsorbents, and achieves efficient recycling of gold in electronic waste, with good stability and selectivity.

CN119016036BActive Publication Date: 2025-03-14JIANGSU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411316505.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-03-14
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing gold adsorbent has low adsorption capacity, slow adsorption rate and low site recognition, making it difficult to effectively recover trace amounts of gold in electronic waste.

Method used

Cross-crunched COF nanocapsule adsorbents are prepared by crystallization and recrystallization strategy. The crystallization and structural order of COF are improved through room temperature crystallization and high temperature recrystallization techniques, thereby improving its adsorption performance.

Benefits of technology

It significantly improves the adsorption rate and adsorption capacity of the adsorbent, is suitable for the separation of complex environments and low-concentration precious metals, has good stability and selectivity, and achieves efficient recycling of gold in electronic waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119016036B_ABST
    Figure CN119016036B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation of adsorption separation functional materials, and discloses a controllable preparation method of a cross-shrinkage COF nanocapsule and an application of selective separation of gold. The method uses 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 2,5-divinylterephthalaldehyde (Dva) as monomers, first crystallizes at room temperature, then recrystallizes at high temperature, and then uses meso-2,3-dimercaptosuccinic acid (DMSA) as a functional monomer to controllably prepare a cross-shrinkage COF nanocapsule adsorbent (C-R-COF@DMSA). This method not only achieves controllable morphology, but also greatly improves adsorption performance. The present invention has important economic value in the field of precious metal recovery, can effectively deal with the waste of precious metal resources and environmental pollution in electronic waste, and provides a new idea for designing low-cost high-performance adsorbents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of adsorption separation functional materials, and relates to a controllable preparation method of cross-shrinkage COF nanocapsules and the application of selective separation of gold. Background Art

[0002] Gold is widely used in jewelry, currency, electronic devices, and chemical catalysis due to its excellent physical and chemical properties. However, the large consumption of gold by industry and society has led to an increase in the demand for gold mining and recycling. In recent years, with the acceleration of the renewal of electronic products, a large amount of electronic waste has been generated. The gold content in the leachate of these electronic wastes is about 1-2000ppm, which is much higher than the 1-30ppm in natural ores. Therefore, the extraction of gold from electronic waste has important environmental significance and considerable economic potential. However, the complexity of the gold recovery process is exacerbated by the presence of metals that compete with gold, such as palladium, copper, silver, chromium, aluminum, and cobalt, which highlights the urgency of developing extremely selective and effective gold recovery methods.

[0003] Adsorption has long been hailed as one of the key and efficient methods for recovering trace gold from electronic waste. Its reputation is based on cost-effectiveness, safety, and environmentally friendly properties. The appeal of this method is further enhanced by its simple operation and suitability for continuous processes. The core of adsorption technology lies in the properties of the adsorbent material, which is a key factor affecting its adsorption performance. However, common adsorbents have defects such as low adsorption efficiency and poor regeneration ability, which limit their scope of application. Therefore, it is particularly necessary to study new adsorbents with excellent adsorption capacity. Covalent organic frameworks (COFs), as a new type of crystalline porous polymers, have attracted widespread attention due to their well-defined crystal structure, customizable porosity, strong chemical and thermodynamic stability, and easily customized functions.

[0004] Although there have been some preliminary explorations in the application of covalent organic frameworks (COFs) in the separation and recovery of gold, the classical solvent thermal synthesis requires strict synthesis conditions, and the morphology and size of the material cannot be controlled. Therefore, we used 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 2,5-divinylterephthalaldehyde (Dva) as monomers to explore the effects of crystallization temperature and recrystallization process temperature on the morphology and properties of COF-V materials, and then functionalized them for the adsorption and separation of gold. This scheme has not been reported yet. Summary of the invention

[0005] In order to solve the problems of low adsorption capacity, slow adsorption rate and low site recognition of gold adsorbents in the prior art, the present invention provides a method for controllably preparing cross-shrinkage COF nanocapsule adsorbent based on a crystallization-recrystallization strategy. 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 2,5-divinylterephthalaldehyde (Dva) are used as monomers, first crystallized at room temperature, then recrystallized at high temperature, and then meso-2,3-dimercaptosuccinic acid (DMSA) is used as a functional monomer to controllably prepare cross-shrinkage COF nanocapsules and apply them to efficiently capture gold in electronic waste liquid.

[0006] In order to achieve the above technical purpose, the technical solution adopted by the present invention is as follows:

[0007] A controllable preparation method of cross-shrinkage COF nanocapsules comprises the following steps:

[0008] (1) Preparation of T1-COF

[0009] First, 1,3,5-tri(4-aminophenyl)benzene (TAPB) and 2,5-divinylterephthalaldehyde (Dva) are added to acetonitrile (ACN) and completely dispersed by ultrasound; then acetic acid (HAc) is added, and after ultrasonic dispersion, the mixture is allowed to stand at temperature T1 for reaction and crystallization time t1; the yellow precipitate obtained is collected by centrifugation and washed several times with tetrahydrofuran THF and ethanol, and finally, the powder is vacuum dried to obtain T1-COF.

[0010] (2) Preparation of T1-T2-COF

[0011] The T1-COF prepared in step (1) is placed in a round-bottom flask, followed by the addition of mesitylene and 1,4-dioxane, and is completely dispersed by ultrasound; deionized water and HAc are then added, and after ultrasonic dispersion, the mixture is reacted at a temperature T2 for a crystallization time t2; the dark yellow precipitate obtained is collected by centrifugation, and washed several times with THF and ethanol, and finally, the powder is vacuum dried to obtain T1-T2-COF.

[0012] (3) Preparation of T1-T2-COF@DMSA

[0013] The T1-T2-COF obtained in step (2) is added to 1,4-dioxane and completely dispersed by ultrasound; then, meso-2,3-dimercaptosuccinic acid (DMSA) and azobisisobutyronitrile (AIBN) are added, and after ultrasonic dispersion, N2 is introduced for time t3, and then the reaction is carried out at a temperature T3 and a rotation speed r for time t4. The solid obtained by centrifugation is separated, washed with THF and ethanol several times, and then placed in a vacuum oven to be fully dried to obtain T1-T2-COF@DMSA.

[0014] In step (1), the dosage ratio of TAPB, Dva, ACN and HAc is 0.02-0.06mmol:0.03-0.09mmol:3-8mL:300-700μL, the temperature T1 is 15-35°C, and the reaction time t1 is 2-10h.

[0015] In step (2), the amount ratio of T1-COF, mesitylene, 1,4-dioxane, deionized water and HAc is 20 mg: 1-3 mL: 4-12 mL: 0.2-3.0 mL: 0.2-2.0 mL, the temperature T2 is 50-90° C., and the reaction crystallization time t2 is 24-72 h.

[0016] In step (3), the usage ratio of T1-T2-COF, 1,4-dioxane, DMSA and AIBN is 10-50 mg: 5-15 mL: 10-100 mg: 5-15 mg.

[0017] t3 is 10-20min, temperature T3 is 60-90°C, rotation speed r is 200-400rpm, and reaction time t4 is 24-72h.

[0018] In steps (1) to (3), the vacuum drying temperature is 60° C. and the time is 24 h.

[0019] The cross-shrinkage COF nanocapsules prepared by the invention are used for selectively separating gold from electronic waste liquid.

[0020] The beneficial effects of the present invention are:

[0021] Solve the problem of precious metal recycling: Since the content of precious metal gold in electronic waste is relatively high, the adsorbent of the present invention is designed and prepared for the precious metals in electronic waste. This helps to efficiently recycle the precious metals in electronic waste and meets the demand for efficient recycling of resources.

[0022] Utilizing crystallization-recrystallization technology: This invention innovatively proposes a crystallization-recrystallization technology, which greatly enhances the crystallinity of covalent organic frameworks (COFs) by first crystallizing at room temperature and then recrystallizing at high temperature. This double crystallization strategy not only significantly improves the crystallinity of COFs, but also further optimizes the orderliness of its structure, thereby significantly improving its adsorption performance and showing a more excellent application prospect.

[0023] The COF prepared by the present invention using the crystallization-recrystallization technology as a strategy has high crystallinity and a double mesoporous structure, which significantly enhances its adsorption rate and adsorption capacity for gold.

[0024] Applicable to complex environments and low-concentration precious metals: Traditional adsorption technology faces challenges when facing low-concentration precious metals, complex competing ions and extremely acidic environments. Due to the introduction of specific binding sites, the adsorbent provided by the present invention still performs well under these conditions and has good stability and adaptability.

[0025] In summary, the present invention has significant economic benefits in the field of precious metal recovery and can effectively address the problems of precious metal resource waste and environmental pollution in electronic waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 1 is a scanning electron microscope image of the material prepared at different recrystallization temperatures in Example 1.

[0027] Figure 2 1 is the X-ray diffraction pattern of the material prepared at different crystallization temperatures in Example 1.

[0028] Figure 3 1 is the X-ray diffraction pattern of the material prepared at different recrystallization temperatures in Example 1.

[0029] Figure 4 This is the infrared spectra of the 35-COF, 35-70-COF and 35-70-COF@DMSA materials prepared in Example 1.

[0030] Figure 5 The effect of pH value on the adsorption capacity of gold ions by the 35-70-COF@DMSA adsorbent prepared in Example 1.

[0031] Figure 6 The adsorption kinetics of gold ions by the 35-70-COF@DMSA adsorbent prepared in Example 1 and its model fitting curve.

[0032] Figure 7 The effect of temperature on the adsorption equilibrium of gold ions by the 35-70-COF@DMSA adsorbent prepared in Example 1 and its model fitting curve.

[0033] Figure 8 This is the adsorption selectivity of the 35-70-COF@DMSA adsorbent prepared in Example 1.

[0034] Fig. 9 This is the adsorption regeneration performance of the 35-70-COF@DMSA adsorbent prepared in Example 1. DETAILED DESCRIPTION

[0035] In the specific implementation of the present invention, the recognition performance evaluation is carried out according to the following method: the static adsorption experiment is used to complete. The adsorption capacity of 1.0 mg of 35-70-COF@DMSA for gold ions is tested in the pH range of 1.0-7.0, and the content of gold ions after adsorption is measured by inductively coupled plasma emission spectrometer, and the optimal adsorption pH is determined according to the results; secondly, the effect of adsorption time on the adsorption capacity of 35-70-COF@DMSA is studied, and the data are fitted, calculated and analyzed using Pseudo first-order model, Pseudo second-order model, etc.; in order to study the maximum adsorption capacity of 35-70-COF@DMSA, we conducted an adsorption equilibrium test in the range of 100-600 ppm of gold ion concentration, and fitted the adsorption data using Langmuir model and Freundlich model, and calculated the adsorption capacity according to the results; and the printed circuit board is selected as the actual sample to study the selective adsorption performance of 35-70-COF@DMSA; finally, its adsorption regeneration performance is tested.

[0036] The present invention will be further described below in conjunction with specific implementation examples.

[0037] Embodiment 1:

[0038] (1) Preparation of 35-COF

[0039] First, 1,3,5-tris(4-aminophenyl)benzene (TAPB, 0.04mmol) and 2,5-divinylterephthalaldehyde (Dva, 0.06mmol) were added to 5mL acetonitrile (ACN) and dispersed completely by ultrasound. Then, 500μL of acetic acid (HAc) was added, and after ultrasound for 1 minute, the mixture was allowed to stand at 35°C for reaction and crystallization for 6h. The obtained yellow precipitate was collected by centrifugation and washed three times with tetrahydrofuran (THF) and ethanol. Finally, the powder was dried under vacuum at 60°C for 24h to obtain 35-COF.

[0040] 15-COF and 25-COF were synthesized in the same procedure by adjusting to the corresponding crystallization temperatures.

[0041] (2) Preparation of 35-70-COF

[0042] 20 mg of 35-COF prepared in step (1) was placed in a round-bottom flask, followed by the addition of 2 mL of mesitylene and 8 mL of 1,4-dioxane, and ultrasonication was performed to completely disperse the mixture. Subsequently, 500 μL of deionized water and 500 μL of HAc were added, and the mixture was ultrasonicated for 3 minutes and then reacted and crystallized at 70°C for 48 hours. The obtained dark yellow precipitate was collected by centrifugation and washed three times with THF and ethanol. Finally, the powder was vacuum dried at 60°C for 24 hours to obtain 35-70-COF.

[0043] 35-50-COF, 35-60-COF, 35-80-COF and 35-90-COF were synthesized in the same procedure by adjusting to the corresponding recrystallization temperatures.

[0044] (3) Preparation of 35-70-COF@DMSA

[0045] 20 mg of 35-70-COF was added to 10 mL of 1,4-dioxane and dispersed completely by ultrasound. Then 50 mg of meso-2,3-dimercaptosuccinic acid (DMSA) and 10 mg of azobisisobutyronitrile (AIBN) were added, and N2 was introduced for 15 min after ultrasound for 3 minutes. Then the mixture was reacted at 80 ° C and 300 rpm for 48 h. The solid was separated by centrifugation, washed several times with THF and ethanol, and then dried in a vacuum oven to obtain 35-70-COF@DMSA.

[0046] Figure 1 Shown are scanning electron microscope images of the materials prepared at different recrystallization temperatures in Example 1, from which it can be seen that as the recrystallization temperature increases, the morphology first becomes spherical, then gradually collapses into cross-wrinkled nanocapsules and finally becomes spherical again.

[0047] Figure 2 Shown are X-ray diffraction patterns of the material prepared at different crystallization temperatures in Example 1, from which it can be seen that as the crystallization temperature increases, the crystallization performance of the material improves accordingly.

[0048] Figure 3 Shown are X-ray diffraction patterns of the material prepared at different recrystallization temperatures in Example 1, from which it can be seen that with the increase of the recrystallization temperature, the crystallization properties of the material show a trend of first increasing and then decreasing, among which the crystallization properties are optimal at 70°C.

[0049] Figure 4 The infrared spectra of 35-COF, 35-70-COF and 35-70-COF@DMSA prepared in Example 1 are shown at 1607 cm -1 The absorption peak of C=N appeared at , confirming the successful preparation of COF material.

[0050] Embodiment 2:

[0051] (1) Preparation of 35-COF

[0052] First, 1,3,5-tris(4-aminophenyl)benzene (TAPB, 0.02mmol) and 2,5-divinylterephthalaldehyde (Dva, 0.03mmol) were added to 3mL acetonitrile (ACN) and dispersed completely by ultrasound. Then, 300μL of acetic acid (HAc) was added, and after ultrasound for 1 minute, the mixture was allowed to stand at 35°C for reaction and crystallization for 2h. The yellow precipitate obtained was collected by centrifugation and washed three times with tetrahydrofuran (THF) and ethanol. Finally, the powder was dried under vacuum at 60°C for 24h to obtain 35-COF.

[0053] 15-COF and 25-COF were synthesized in the same procedure by adjusting to the corresponding crystallization temperatures.

[0054] (2) Preparation of 35-70-COF

[0055] 20 mg of 35-COF prepared in step (1) was placed in a round-bottom flask, followed by the addition of 1 mL of mesitylene and 4 mL of 1,4-dioxane, and the mixture was dispersed completely by ultrasound. Subsequently, 200 μL of deionized water and 200 μL of HAc were added, and the mixture was subjected to ultrasound for 3 minutes and then crystallized at 70°C for 24 hours. The obtained dark yellow precipitate was collected by centrifugation and washed three times with THF and ethanol. Finally, the powder was dried under vacuum at 60°C for 24 hours to obtain 35-70-COF.

[0056] 35-50-COF, 35-60-COF, 35-80-COF and 35-90-COF were synthesized in the same procedure by adjusting to the corresponding recrystallization temperatures.

[0057] (3) Preparation of 35-70-COF@DMSA

[0058] 10 mg of 35-70-COF was added to 5 mL of 1,4-dioxane and dispersed completely by ultrasound. Then 10 mg of meso-2,3-dimercaptosuccinic acid (DMSA) and 5 mg of azobisisobutyronitrile (AIBN) were added, and N2 was introduced for 10 min after ultrasound for 3 minutes. Then the reaction was carried out at 60 ° C and 200 rpm for 24 hours. The solid was separated by centrifugation, washed several times with THF and ethanol, and then placed in a vacuum oven to be fully dried to obtain 35-70-COF@DMSA.

[0059] Embodiment 3:

[0060] (1) Preparation of 35-COF

[0061] First, 1,3,5-tris(4-aminophenyl)benzene (TAPB, 0.06mmol) and 2,5-divinylterephthalaldehyde (Dva, 0.09mmol) were added to 8mL acetonitrile (ACN) and dispersed completely by ultrasound. Then, 700μL of acetic acid (HAc) was added, and after ultrasound for 1 minute, the mixture was allowed to stand at 35°C for reaction and crystallization for 2h. The yellow precipitate obtained was collected by centrifugation and washed three times with tetrahydrofuran (THF) and ethanol. Finally, the powder was dried in vacuum at 60°C for 24h to obtain 35-COF.

[0062] 15-COF and 25-COF were synthesized in the same procedure by adjusting to the corresponding crystallization temperatures.

[0063] (2) Preparation of 35-70-COF

[0064] 20 mg of 35-COF prepared in step (1) was placed in a round-bottom flask, followed by the addition of 3 mL of mesitylene and 12 mL of 1,4-dioxane, and ultrasonication was performed to completely disperse the mixture. Subsequently, 3 mL of deionized water and 2 mL of HAc were added, and the mixture was ultrasonicated for 3 minutes and reacted at 70°C for 72 h. The obtained dark yellow precipitate was collected by centrifugation and washed three times with THF and ethanol. Finally, the powder was vacuum dried at 60°C for 24 h to obtain 35-70-COF.

[0065] 35-50-COF, 35-60-COF, 35-80-COF and 35-90-COF were synthesized in the same procedure by adjusting to the corresponding recrystallization temperatures.

[0066] (3) Preparation of 35-70-COF@DMSA

[0067] 50 mg of 35-70-COF was added to 15 mL of 1,4-dioxane and dispersed completely by ultrasound. Then 100 mg of meso-2,3-dimercaptosuccinic acid (DMSA) and 15 mg of azobisisobutyronitrile (AIBN) were added, and N2 was introduced for 20 min after ultrasound for 3 minutes. Then the reaction was carried out at 90 ° C and 400 rpm for 72 hours. The solid was separated by centrifugation, washed several times with THF and ethanol, and then placed in a vacuum oven to be fully dried to obtain 35-70-COF@DMSA.

[0068] Embodiment 4:

[0069] Accurately weigh 7 portions of 1 mg of 35-70-COF@DMSA prepared under the conditions described in Example 1, and add them to 5 mL of gold ion solution with pH values ​​of 1, 2, 3, 4, 5, and 6 and a concentration of 100 mg / L, respectively, place them on a shaker at 25°C for adsorption for 12 hours, and collect the supernatant. The remaining gold ion concentration in the solution is detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments are performed.

[0070] Figure 5 The effect of pH value on the adsorption capacity of gold ions by the 35-70-COF@DMSA adsorbent prepared in Example 1. It can be seen that the adsorption capacity of 35-70-COF@DMSA is the largest in an environment with a pH of 6, which is about 1737.12 mg g -1 .

[0071] Embodiment 5:

[0072] Accurately weigh 10 portions of 1 mg of 35-70-COF@DMSA, add them to 5 mL of a gold ion solution with a concentration of 400 mg / L and a pH value of 6, place them on a shaker at 25°C and adsorb for 5, 10, 15, 30, 60, 90, 120, 240, 480, and 720 min, and collect the supernatant. The remaining gold ion concentration in the solution was detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments were performed.

[0073] Figure 6 The adsorption kinetics of gold ions by the 35-70-COF@DMSA adsorbent prepared in Example 1 and its model fitting curve. It can be seen that the maximum adsorption capacity of 1742.79 mg g can be reached in about 12 h. -1 .

[0074] Embodiment 6:

[0075] Weigh 6 portions of 1 mg of 35-70-COF@DMSA accurately and add them to 5 mL of gold ion solution (pH 6) with concentrations of 100, 200, 300, 400, 500, and 600 mg / L, respectively. Place them on a shaker at 25°C for 12 hours to adsorb and collect the supernatant; place them on a shaker at 35°C for 12 hours to adsorb and collect the supernatant; place them on a shaker at 45°C for 12 hours to adsorb and collect the supernatant. The remaining gold ion concentration in the solution was detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments were performed.

[0076] Figure 7The effect of temperature on the adsorption equilibrium of gold ions by the 35-70-COF@DMSA adsorbent prepared in Example 1 and its model fitting curve. It can be seen that with the increase of the initial concentration of gold ions, the adsorption capacity of 35-70-COF@DMSA gradually increases. With the increase of temperature, the adsorption capacity of 35-70-COF@DMSA also gradually increases, reaching a maximum of 2474.23 mg g -1 The fitting results of the adsorption data are more consistent with the Langmuir model.

[0077] Embodiment 7:

[0078] Accurately weigh 3 mg of 35-70-COF@DMSA prepared under the conditions described in Example 1, add 5 mL of actual electronic waste liquid (pH = 3) containing Au(III), Pd(Ⅱ), Al(III), Co(II), Cr(III), Cu(II), Na(I), Ni(II), Zn(II), etc., place it on a shaker at 25°C for adsorption for 12 hours, collect the supernatant, and use inductively coupled plasma emission spectrometer (ICP) to detect the residual concentration of various ions in the solution. Three parallel experiments were performed.

[0079] Figure 8 The adsorption selectivity of the 35-70-COF@DMSA adsorbent prepared in Example 1. As can be seen from the figure, 35-70-COF@DMSA has good selectivity for Au.

[0080] Embodiment 8:

[0081] Accurately weigh 10 mg of 35-70-COF@DMSA, add 10 mL of 300 mg / L palladium ion solution with a pH of 6, and place it on a shaker for adsorption at 25°C for 12 hours. After taking the supernatant, remove the solution, wash with deionized water, add 10 mL of eluent prepared with 1 mol / L thiourea and 0.1 mol / L hydrochloric acid, continue to place it on a shaker for desorption for 1.5 hours, then collect the adsorbent by centrifugation, remove the solution, wash with deionized water and dry. This is one cycle, and a total of six cycles are performed. The remaining gold ion concentration in the solution is detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments are performed.

[0082] Fig. 9 This is the adsorption regeneration performance of the 35-70-COF@DMSA adsorbent prepared in Example 1. As can be seen from the figure, after six adsorption cycles, the adsorption efficiency remains basically unchanged.

[0083] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A controllable preparation method of cross-shrinkage COF nanocapsules, characterized in that: The steps include: (1) Preparation of T1-COF First, 1,3,5-tris(4-aminophenyl)benzene TAPB and 2,5-divinylterephthalaldehyde Dva are added to acetonitrile ACN and dispersed completely by ultrasound; then acetic acid HAc is added, and after ultrasonic dispersion, the mixture is allowed to stand at temperature T1 for reaction and crystallization time t1; the yellow precipitate obtained is collected by centrifugation and washed several times with tetrahydrofuran THF and ethanol, and finally, the powder is dried in vacuum to obtain T1-COF; (2) Preparation of T1-T2-COF The T1-COF prepared in step (1) is placed in a round-bottom flask, and then mesitylene and 1,4-dioxane are added and completely dispersed by ultrasound; deionized water and HAc are then added, and after ultrasonic dispersion, the mixture is reacted at a temperature T2 for a crystallization time t2; the dark yellow precipitate obtained is collected by centrifugation, and washed several times with THF and ethanol, and finally, the powder is vacuum dried to obtain T1-T2-COF; (3) Preparation of T1-T2-COF@DMSA The T1-T2-COF obtained in step (2) is added to 1,4-dioxane and completely dispersed by ultrasound; then, meso-2,3-dimercaptosuccinic acid DMSA and azobisisobutyronitrile AIBN are added, and after ultrasonic dispersion, N2 is introduced for time t3, and then the reaction is carried out at a temperature T3 and a rotation speed r for time t4. The solid obtained by centrifugation is separated, washed with THF and ethanol several times, and then placed in a vacuum oven to be fully dried to obtain T1-T2-COF@DMSA.

2. The controllable preparation method according to claim 1, characterized in that: In step (1), the usage ratio of TAPB, Dva, ACN and HAc is 0.02-0.06mmol:0.03-0.09mmol:3-8mL:300-700μL.

3. The controllable preparation method according to claim 1, characterized in that: In step (1), the temperature T1 is 15-35°C and the reaction time t1 is 2-10h.

4. The controllable preparation method according to claim 1, characterized in that: In step (2), the amount ratio of T1-COF, mesitylene, 1,4-dioxane, deionized water and HAc is 20 mg: 1-3 mL: 4-12 mL: 0.2-3.0 mL: 0.2-2.0 mL.

5. The controllable preparation method according to claim 1, characterized in that: In step (2), the temperature T2 is 50-90° C., and the reaction crystallization time t2 is 24-72 h.

6. The controllable preparation method according to claim 1, characterized in that: In step (3), the usage ratio of T1-T2-COF, 1,4-dioxane, DMSA and AIBN is 10-50 mg: 5-15 mL: 10-100 mg: 5-15 mg.

7. The controllable preparation method according to claim 1, characterized in that: In step (3), t3 is 10-20 min, temperature T3 is 60-90° C., rotation speed r is 200-400 rpm, and reaction time t4 is 24-72 h.

8. The controllable preparation method according to claim 1, characterized in that: In steps (1) to (3), the vacuum drying temperature is 60° C. and the time is 24 h.

9. Use of the cross-shrinkage COF nanocapsules prepared by the preparation method according to any one of claims 1 to 8 for selectively separating gold from electronic waste liquid.

Citation Information

Patent Citations

  • Preparation method of electrode based on gold nanoparticle doped covalent organic framework composite material

    CN108362750A

  • Covalent organic framework material as well as preparation method and application thereof

    CN111909389A